Aggregation-Induced Emission: Lighting Up hERG Potassium Channel - Zhang, Xiaomeng; Liu, Tingting; Li, Qi; Li, Minyong; Du, Lupei (Frontiers in Chemistry, 2019)
Based on the scaffold of astemizole and E-4031, four AIE light-up probes (L1-L4) for Human Ether-a-go-go-Related Gene (hERG) potassium channel were developed herein using AIE fluorogen (TPE). These probes showing advantages such as low background interference, superior photostability, acceptable cell toxicity, and potent inhibitory activity, which could be used to image hERG channels at the nanomolar level. These AIE light-up probes hoped to provide guidelines for the design of more advanced AIE sensing and imaging hERG channels to a broad range of applications.